2013
DOI: 10.1088/1054-660x/23/12/126001
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of high-power fiber laser welding based on principal component analysis of a molten pool configuration

Abstract: There exists plenty of welding quality information on a molten pool during high-power fiber laser welding. An approach for monitoring the high-power fiber laser welding status based on the principal component analysis (PCA) of a molten pool configuration is investigated. An infrared-sensitive high-speed camera was used to capture the molten pool images during laser butt-joint welding of Type 304 austenitic stainless steel plates with a high-power (10 kW) continuous wave fiber laser. In order to study the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Since laser welding has gained growing recognition as a key technology in contemporary welding [1][2][3][4], stability monitoring and defect detection during laser welding have become a focus of research in recent years [5][6][7][8]. At present, optical sensing technology has the widest application in laser welding detection [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Since laser welding has gained growing recognition as a key technology in contemporary welding [1][2][3][4], stability monitoring and defect detection during laser welding have become a focus of research in recent years [5][6][7][8]. At present, optical sensing technology has the widest application in laser welding detection [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been experimented to detect the weld position. [8][9][10] For instance, seam tracking system LPF, welding monitor, and RoboFind have been commercialized for several years. The most popular technique used for weld joint detection is based on the principle of optical triangulation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al [11] showed that the periodic oscillation of a plume could be attributed to the oscillation of the keyhole. Gao et al [12] pointed out that the stability of the welding process could be monitored by observing the behavior of the plume. Shcheglov et al [13,14] indicated that the plumes have a remarkable effect on the welding process.…”
Section: Introductionmentioning
confidence: 99%